2020
DOI: 10.1002/iub.2350
|View full text |Cite
|
Sign up to set email alerts
|

Berberine: A novel therapeutic strategy for cancer

Abstract: Cancer, even currently, is one of the main reasons for mortality and morbidity, worldwide. In recent years, a great deal of effort has been made to find efficient therapeutic strategies for cancer, however, particularly with regards to side effects and the possibility of complete remission. Berberine (BBR) is a nature‐driven phytochemical component originated from different plant groups such as Berberis vulgaris, Berberis aquifolium, and Berberis aristata. BBR is a well‐known nutraceutical because of its wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 104 publications
(119 reference statements)
0
47
0
Order By: Relevance
“…Three studies deal with the effect of berberine on myeloma cells applying RPMI8226 and U266 cell lines with miRNA screening methods [ 17 , 18 , 19 ]. Berberine, a well-known isoquinoline alkaloid of the protoberberine type, is distributed among the Berberidaceae, Papaveraceae, and Ranunculaceae plant families and mostly isolated from different Berberis species [ 20 , 21 ]. Berberine is known for its proapoptotic and autophagic potential against many types of cancer but also for its chemosensitizing properties suggesting its use in combination therapy [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies deal with the effect of berberine on myeloma cells applying RPMI8226 and U266 cell lines with miRNA screening methods [ 17 , 18 , 19 ]. Berberine, a well-known isoquinoline alkaloid of the protoberberine type, is distributed among the Berberidaceae, Papaveraceae, and Ranunculaceae plant families and mostly isolated from different Berberis species [ 20 , 21 ]. Berberine is known for its proapoptotic and autophagic potential against many types of cancer but also for its chemosensitizing properties suggesting its use in combination therapy [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Berberine, a well-known isoquinoline alkaloid of the protoberberine type, is distributed among the Berberidaceae, Papaveraceae, and Ranunculaceae plant families and mostly isolated from different Berberis species [ 20 , 21 ]. Berberine is known for its proapoptotic and autophagic potential against many types of cancer but also for its chemosensitizing properties suggesting its use in combination therapy [ 21 , 22 , 23 ]. With regard to MM, berberine downregulated miRNA-21 expression and significantly upregulated programmed cell death 4 (PDCD4) leading to apoptosis and G2 phase cell cycle arrest in RPMI8226 cells [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“… 9 Abundant evidence indicates that the anti-inflammatory effect of BBR relays in the regulation of signaling pathways associated with inflammation. 15 , 22 Cell death and cell cycle arrest of activated rheumatoid arthritis fibroblast-like synoviocytes in combination with an anti-apoptotic influence on chondrocytes were proposed to contribute also to the pharmacological effects of BBR on joint cartilage. 44 , 48 Remarkably, the induction of cell cycle arrest and apoptosis constitutes the basis for the anti-tumoral pharmacological application of BBR in a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 48 Remarkably, the induction of cell cycle arrest and apoptosis constitutes the basis for the anti-tumoral pharmacological application of BBR in a variety of tumors. 15 These pharmacological effects have been associated with transcriptional regulation of the pro-apoptotic and tumor suppressor genes, such as p53, p21 , or Bax via inducing epigenetic modifications. 15 , 24 , 48 These modifications included changes in DNA methylation, 23 inhibition of histone deacetylases binding, 24 inhibition of the epigenetic regulatory factor Uhrf1 , 25 and transcriptional up-regulation of demethylation (TET) enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine shows a good therapeutic effect on ulcerative colitis (Jing et al, 2020) and can improve glucose metabolism and insulin resistance by suppressing the inflammatory response (Shan et al, 2020). Recent studies have shown that BBR also has anti-tumor effects, such as promoting autophagy, anti-proliferation, apoptosis and so on (Liu J. et al, 2020;Samadi et al, 2020). However, the therapeutic effect of BBR on MNNG-induced CAG and its potential mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%